The Ino80 complex mediates epigenetic centromere propagation via active removal of histone H3 - Eun Shik Choi (Nature Portfolio, 2017)
The histone variant CENP-A marks active centromeres and replaces H3 at centromeres through a poorly understood mechanism. Here, the authors provide evidence that the chromatin remodeller Ino80 promotes CENP-A chromatin assembly at the centromere in fission yeast.